Health Inequality Analysis and Social Determinants within Urban Area - สังข์จ่าง, ชัยณรงค์ (Journal of Health Science of Thailand, 2020)
The objective of this study was to analyze health inequality of urban population and social determinants of health relating to societal context and structural factors. The methodology involved the comparative analysis of health risk opportunity and difference in socio-economic status of people. Data were collected from the reports of the health and welfare survey 2011 conducted by the National Statistical Office; and 36,564 samples of urban population in all municipalities of Thailand and Bangkok Metropolitan Administration were included. Data analysis was performed by logistic regression statistic using STATA® software ver.11 for Mac. The study revealed inequality of health opportunity within urban population with varying degrees of magnitude and distribution pattern. Such inequality was significantly associated with social determinants which included regional setting and some structural factors such as socioeconomic stratification, gender, marital status, educational level, occupation, economic class and income categories (p<0.05). Thus, it is essential that local and regional administrative organizations should pay attention and take part in the formulation of policies and goals to systematically eliminate health inequality in the urban settings. In addition, effective information system should be developed to improve efficiency on the creation of evidences to support policy formulation as well as monitoring and evaluzation of the policy and program implementation.